Summary of the speeches and presentations of the “Open Seminar on RDA in Europe: a reality and a challenge” - Gabriele Meßmer (JLIS.it, 2018)
Two days prior to the EURIG annual meeting 2017 the University of Florence and Casalini Libri hosted the Open Seminar on RDA in Europe.. The international cataloguing code Resource Description and Access (RDA) has the potential to become a popular, globally used standard and to connect library data with data from other communities. This short article summarizes the speeches and presentations of the seminar held on May 8, 2017 in the Aula Magna, University of Florence.